'A pretty bad reputation': reflections of 'the 31 March incident' on Ottoman Syria, its background, and its immediate consequences. Issue 3 (4th May 2023) - Sezer, Selim
Abstract: This article elaborates how the Islamist-led revolt that erupted in Istanbul in April 1909 against the Committee of Union Progress was reflected in cities of Ottoman Syria, as well as its sources and the immediate results in terms of relations between the policymakers in Istanbul and the elites of Syria. Using primary sources such as Ottoman journals and archival documents together with several secondary sources concerning various aspects of that process, the article gives a descriptive narrative about the revolt/coup attempt itself, the events experienced in Syria and its aftermath on one hand. On the other hand, it tries to reveal the origins of the relative support given to the revolt in Syria by trying to draw a general picture of the Syrian region in late Ottoman period, taking in consideration various analyses in the existing literature in a critical way. The article claims that the revolt was supported in cities like Damascus and Nablus for both ideological and deep-rooted social reasons. It also shows how the Committee of Union of Progress, which was already prejudiced against Syrian Arabs, adopted an even more negative stance and closed one of their organizations which became in fact a scapegoat.